Optic disc - fovea distance, axial length and parapapillary zones: the Beijing Eye Study 2011 - Jonas, Rahul A.; Jonas, Jost B. (PLOS ONE, 2015)
Purpose: To measure the distance between the optic disc center and the fovea (DFD) and to assess its associations. Methods: The population-based cross-sectional Beijing Eye Study 2011 included 3468 individuals aged 50+ years. The DFD was measured on fundus photographs. Results: Readable fundus photographs were available for 2836 (81.8%) individuals. Mean DFD was 4.76 ± 0.34mm (median: 4.74 mm; range: 3.76-6.53mm). In multivariate analysis, longer DFD was associated with longer axial length (P<0.001; standardized correlation coefficient beta: 0.62), higher prevalence of axially high myopia (P<0.001; beta:0.06), shallower anterior chamber depth (P<0.001; beta:-0.18), thinner lens thickness (P = 0.004; beta: -0.06), smaller optic disc-fovea angle (P = 0.02; beta: -0.04), larger parapapillary alpha zone (P = 0.008; beta: 0.05), larger parapapillary beta/gamma zone (P<0.001; beta: 0.11), larger optic disc area (P<0.001; beta: 0.08), lower degree of cortical cataract (P = 0.002; beta: -0.08), and lower prevalence of age-related macular degeneration (P = 0.001; beta: -0.06). Bruch´s membrane opening-fovea distance (DFD minus disc radius minus parapapillary beta/gamma zone width) in non-glaucomatous eyes was not significantly (P = 0.60) related with axial length in emmetropic or axially myopic eyes (axial length ≥23.5 mm), while it increased significantly (P<0.001; r: 0.32) with longer axial length in eyes with an axial length of <23.5mm. Ratio of mean DFD to disc diameter was 2.65 ± 0.30. If the ratio of disc-fovea distance to disc diameter was considered constant and if the individual disc diameter was calculated as the individual disc-fovea distance divided by the constant factor of 2.65, the resulting calculated disc diameter differed from the directly measured disc diameter by 0.16 ±0.13 mm (median: 0.13 mm, range: 0.00-0.89 mm) or 8.9 ± 7.3% (median: 7.4%; range: 0.00-70%) of the measured disc diameter. Conclusions: DFD (mean: 4.76mm) increases with longer axial length, larger parapapillary alpha zone and parapapillary beta/gamma zone, and larger disc area. The axial elongation associated increase in DFD was due to an enlargement of parapapillary beta/gamma zone while the Bruch’s membrane opening-fovea distance did not enlarge with longer axial length. This finding may be of interest for the process of emmetropization and myopization. Due to its variability, the disc-fovea distance has only limited clinical value as a relative size unit for structures at the posterior pole.
Gesehen am 01.03.2018